Ethanol Extract of Brucea javanica Seed Inhibit Triple-Negative Breast Cancer by Restraining Autophagy via PI3K/Akt/mTOR Pathway - Chen, Xiaohong; Li, Shuang; Li, Dan; Li, Muxia; Su, Ziren; Lai, Xiaoping; Zhou, Changlin; Chen, Shaodan; Li, Shunxian; Yang, Xiaobing; Su, Jiyan; Zhang, Yunjian (Frontiers in Pharmacology, 2020)
Triple-negative breast cancer (TNBC) is an aggressive disease with worst prognosis than other subtypes of breast cancer. Owing to the lack of hormone receptors and HER2 expression on TNBC cells, patients do not have targeted therapy options available with other breast cancer subtypes. Extensive efforts have been made to identify novel therapeutics against TNBC. Interestingly, recent studies had shown that plant-derived natural products could modulate the autophagy and induce the breast cancer cells death. Seed of Brucea javanica has been used as an important traditional Chinese medicine against cancers. In the present study, the anti-breast cancer potential of ethanol crude extracts from B. javanica seed (BJE) was explored. Data demonstrated that BJE could inhibit the TNBC cell line MDA-MB-231 proliferation and induced apoptosis. In the cells exposed to BJE, protein expressions of UNC-51-like kinase -1 (ULK1) and Beclin-1 and the ratio of light chain 3 II/I (LC3 II/I) were reduced, while the expression of p62 was increased, indicating an inhibition on autophagy. Moreover, BJE promoted the phosphorylation of mammalian target of rapamycin (mTOR), phosphatidylinositol 3-kinase (PI3K), and Akt in MDA-MB-231. BJE also suppressed the MDA-MB-231 tumor growth in vivo. Coincide with the results in vitro, autophagy in the tumor tissue was weakened as indicated by decreased ratio of LC 3 II/I and Beclin-1 accompanied by enhanced phosphorylation of mTOR, which confirmed that autophagy restraint via the PI3K/Akt/mTOR signaling pathway contributes to the suppression by BJE. Notably, no noticeable toxicity in non-targeted organs was found, including small intestine, liver, and kidney. Taken together, this study revealed anti-breast cancer activity of BJE based on autophagy restraint, highlighting its clinical importance as a novel natural agent against TNBC.